Informed Decision-Making through Forecasting: A Practitioner’s Guide to Government Revenue Analysis by Shayne C. Kavanagh and Daniel W. Williams - Joseph Vonasek (Journal of Public and Nonprofit Affairs, 2017)
Kavanagh, S. C., & Williams, D. W. (2017). Informed Decision-Making through Forecasting: A Practitioner’s Guide to Government Revenue Analysis. Chicago, IL: Government Finance Officers Association. $90.00 (paperback), ISBN: 978-0-89125-002-9.